Subsidizing Purchase of Apartments and Residential Construction - Baturan, Luka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
During last few years, Republic of Serbia has been allowing significant resources for subsidizing purchase of apartments and residential construction. Explanation for this is desire to help construction sector to overcome consequences of economic crisis, as well as social categories to solve housing issue. The paper analyzes economic consequences, benefits and costs of conducting this economic policy, as well as reasons leading to its establishment.